(3TQM OjhGf YdbeI GdaMd(B((3QhGjI GdCUeYj(B)s - (3CHi HcQ YGUe Hf CjhH GdHWdjhSis; (3YdbeI Hf YHOI (B((3HaJM GdYjf hGdHGA(B) (3Hf fGTQI Hf bjS, ef Hfj Jeje,fMh (B20 (3b g`s
(3ChdgG (B:s
(3bGd YdbeI Hf YHOI hgh GdPi jbGd dg GdaMd dCfg Nda GeQF GdbjS Ydi GeQCJg hbjd Ef ai QgWg QLdkG jbGd dg YdbeI GdNUi s
(3BNQgG (B:s
(3cGf PQGYjgG Ydi GdNd HYOeG hHjf PQGYG eGJM eJLQO JeJ TQM GdbUjOI ced TYQ YdbeI GHf YHOI s
(3fSNI KGfjI JJab ai ChdgG hBNQgG eY GdfSNI GdChdi HGNJdGa ai HYV GdCdaGXs
(3hHBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdCOHs